Factors Affecting Reuse Interest among Shopeepay Users in Alfamart Consumers - Ana Laila Shofyana; Sutono; Mia Ajeng Alifiana (Jurnal Manajemen Sains dan Organisasi, 2023)
Purpose - This study aims to determine the effect of sales promotions, price perceptions, and ease of transaction on the intention to reuse through consumer satisfaction (studies on Alfamart consumers who use Shopeepay in Kudus). Design/Methodology/Approach - This type of research is quantitative research. The population in this study are Alfamart consumers using Shopeepay in Kudus. The sample used was 156 respondents using a purposive sampling technique. Data analysis in this study was Structural Equation Modeling (SEM) with the AMOS assistance program.   Findings - Based on the results of the study it can be concluded that:1) Sales promotion has a positive and significant effect on consumer satisfaction; 2) Perceived price has a positive and significant effect on consumer satisfaction; 3) Ease of transaction has a positive and significant effect on customer satisfaction; 4) Sales promotion has a positive and significant effect on the intention to reuse; 5) Perceived price has a positive and significant effect on the intention to reuse; 6) The ease of transaction has a positive and significant effect on the intention to reuse; and 7) consumer satisfaction has a positive and significant effect on the intention to reuse. Keywords: Reuse Interest, Sales Promotion, Price Perceptions, Ease of Transaction